FAKTOR-FAKTOR YANG MEMPENGARUHI BOARD SIZE SEKTOR PERUSAHAAN MANUFAKTUR - Johannes Alvin Lieyanto; Vidyarto Nugroho (Jurnal Paradigma Akuntansi, 2026)
The purpose of this empirical research is to examine the effect of profitability, firm size, leverage, and board of commissioners size on manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study uses 78 manufacturing companies selected by purposive sampling method with a total of 312 data in four years. This study uses panel data regression analysis. The results of this study are profitability has a positive effect on cash holding, leverage has a negative effect on cash holding, company size has a positive effect on cash holding, board size has a negative effect on cash holding.